FOLFOX‐bevacizumab chemotherapy in patients with metastatic neuroendocrine tumors. (4th January 2023) - Lacombe, Caroline; Perrier, Marine; Hentic, Olivia; Brixi, Hedia; De Rycke, Ophélie; Cros, Jérôme; Rebours, Vinciane; Cadiot, Guillaume; Ruszniewski, Philippe; de Mestier, Louis
Abstract: Neuroendocrine tumors (NETs) are highly vascularized neoplasms. While FOLFOX chemotherapy has shown efficacy in patients with advanced NETs, its combination with antiangiogenics has been scarcely described. Here, we report the efficacy and tolerance of FOLFOX‐bevacizumab in this setting. We retrospectively studied all consecutive patients with metastatic NET treated by FOLFOX‐bevacizumab in two expert centers from 2013 to 2020. We assessed time to treatment failure (TTF), objective response rate (ORR) and toxicity. We explored factors associated with TTF and ORR using multivariate analyses. We included 57 patients (35.1% female, median age 61.7 years), with pancreatic (66.7%), small‐intestine (14%) or lung (7%) NETs. Most patients (57.9%) had extra‐hepatic metastases and G3 NETs accounted for 40.3% of cases. Patients received a median of 17 cycles of treatment, including a median of seven cycles of bevacizumab and/or 5‐fluorouracile maintenance. Median TTF was 15.5 months (95% CI: 9.8–21.2) and was shorter in patients age > 60 years (HR 2.56, 95% CI: 1.16–5.64), p = .020) and >1 previous systemic treatment line (HR 4.15, 95% CI: 1.96–8.78), p < .001). The ORR was 42.9% and was higher in cases of performance status at 0 (OR 5.25, 95% CI: 1.13–24.35), p = .034) and G3 NET (OR 5.39, 95% CI: 1.23–23.52), p = .025). The FOLFOX‐bevacizumab combination has promising efficacy in patients with progressive metastatic NETs and notably for G3 NETs, for which optimal treatment as yet remains ill‐defined. Hence, it could be a relevant alternative to alkylating‐based chemotherapy in this setting and should be further explored prospectively. Abstract : Waterfall plot of the maximal change in size of target lesions, in 56 patients with metastatic NETs treated by FOLFOX‐bevacizumab, depending on their primary tumor origin and tumor grade (morphological response was not evaluable in one patient).